Amino Acid Profile of Polymeric Formula Based on Local Food for Stunting Prevention - Hendrayati, Hendrayati; Adam, Adriyani; Fauziah, Fauziah (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Adequacy energy and protein  has a very strong potential to prevent stunting in children. The role of protein in preventing stunting can be focused more on the amino acid content of a food. Metabolomic research has proven that children who are stunted have lower serum concentrations of nine essential amino acids (tryptophan, isoleucine, leucine, valine, methionine, threonine, histidine, phenylalanine, lysine) compared to children who are not stunted ( p < 0.01). In addition, children who are stunted have low serum concentrations of conditionally essential amino acids (arginine, glycine, glutamine), non-essential amino acids (asparagine, glutamate, serine).This research was to ingredients the amino acid content (glutamic acid, phenylalanine, isoleucine, alanine, arginine, lysine, leucine, threonine, cystine, histidine) in polymeric formulas developed from local food. This research uses an experimental design in the laboratory with a Randomized Complete Factorial (RCF) with four factors, namely F1, F2, F3 and F4. The difference between the formulations of these four formulas is the addition of full cream milk (0%, 10%, 20% and 30% ) Analysis of the amino acid content was carried out at the SIG Laboratory Bogor.  Results showed that the types of essential amino acids were complete and had a good quality amino acid score (SAA=100%). The limiting amino acid is the amino acid lysine. The digestible amino acid score in each formula is; F1 (65.72%), F2 (73.43%), F3 (81.53%), and F4 (85.25%).The results of the one-way ANOVA test showed that there were differences in amino acid content in the four formulas (P>0.05). Follow-up tests used the Tukey test to determine pairwise differences between groups and all groups, showing constant results. This shows that the treatment given, namely the addition of full cream milk, had a significant effect on the differences in amino acid content in the four formulas. Conclusion: The polymeric formula developed contains complete and good quality amino acids.